INVESTIGATING INFECTION'S ROLE AS A CONTRIBUTING FACTOR IN THE GENETIC AND EPIGENETIC MECHANISMS OF ENDOMETRIOSIS: A NARRATIVE REVIEW. - Archana Jha (Student's Journal of Health Research Africa, 2024)
Endometriosis is a chronic gynecological condition, characterized by the presence of endometrial-like tissue outside the uterus. It is associated with symptoms such as pelvic pain, dysmenorrhea, and infertility, significantly impacting women's quality of life. Despite its prevalence, the pathophysiology of endometriosis is not fully understood, with genetic, epigenetic, environmental, immunological, and hormonal factors all playing roles in its development. This review aims to systematically examine the evidence linking infections to the genetic and epigenetic mechanisms of endometriosis, highlighting how these interactions may contribute to the disease's development and progression. Recent research has identified a connection between genetic predispositions to endometriosis and an enhanced immune response to infections. Specific genetic markers associated with an increased risk of endometriosis have also been linked to heightened immune reactions to infectious agents, suggesting a complex interplay between endometriosis and infections. Variations in genes regulating the immune system and inflammatory processes, such as the Toll-like receptor 4 (TLR4), have been implicated in both endometriosis and the body's response to infections. Furthermore, infections can induce epigenetic changes that may influence the development and severity of endometriosis by altering gene expression related to inflammation, immune surveillance, and tissue repair. Understanding the relationship between infections, genetic predispositions, and epigenetic modifications in endometriosis opens new avenues for research into targeted therapies. Addressing the underlying genetic and immunological factors contributing to endometriosis could lead to more effective treatment strategies, potentially improving the quality of life for those affected by the condition. Clinicians should consider the potential role of infections in the exacerbation of endometriosis symptoms and the importance of comprehensive patient evaluations to identify and treat any concurrent infections. Future therapeutic strategies should also explore anti-inflammatory therapies and preventive measures against pathogens known to influence endometriosis progression.